2004
DOI: 10.1038/sj.eye.6701472
|View full text |Cite
|
Sign up to set email alerts
|

Inter-device reproducibility of the scanning laser polarimeter with variable cornea compensation

Abstract: Objective To evaluate the interdevice reproducibility of retinal nerve fibre layer (RNFL) thickness measurements obtained with the commercially available GDx-VCC, a scanning laser polarimeter with variable (individualized) corneal compensation. Methods A prospective instrument validation study in which 13 GDx-VCC devices were tested. One eye each, from three normal subjects were used to test each of the devices, on the same day, by an experienced operator. Variability and reproducibility for each of five GDx p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
0
10
0
5
Order By: Relevance
“…SLP was shown to be a highly reproducible imaging technique of the RNFL. [9][10][11] After experience with the GDx-VCC accumulated, it became apparent that an additional SLP anomaly, which is likely unrelated to corneal compensation, appears in a small proportion of scanned individuals. 12 This SLP anomaly, or artefact, became known as an atypical birefringence pattern (ABP), and consequently has been addressed by the manufacturer via a typical scan score (TSS) score (on a scale of 0-100), such that normal patterns score high, while ABP scans score low.…”
Section: Introductionmentioning
confidence: 99%
“…SLP was shown to be a highly reproducible imaging technique of the RNFL. [9][10][11] After experience with the GDx-VCC accumulated, it became apparent that an additional SLP anomaly, which is likely unrelated to corneal compensation, appears in a small proportion of scanned individuals. 12 This SLP anomaly, or artefact, became known as an atypical birefringence pattern (ABP), and consequently has been addressed by the manufacturer via a typical scan score (TSS) score (on a scale of 0-100), such that normal patterns score high, while ABP scans score low.…”
Section: Introductionmentioning
confidence: 99%
“…This parameter is a support vector machine algorithm, automatically provided by the device software, and calculated combining information from many different parameters. In previous reports NFI displayed moderate to low reproducibility levels [27, 29]. We may postulate that even slight intersession differences for those parameters may influence NFI value through a summation effect.…”
Section: Discussionmentioning
confidence: 99%
“…Overall results were fair to good. The most recent version of SLP, coupled with a variable corneal compensator, has been evaluated in terms of interdevice reproducibility and reliability of measures [27], interoperator reproducibility and any operator learning effect in 15 normal and 15 glaucomatous patients [28] and intraobserver reproducibility in healthy eyes and eyes with ocular hypertension [29]. To our knowledge, evaluation of intersession reproducibility is lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Some have reported that pupillary size does not affect the statistical evaluation of the parameters associated with polarimetric assessment of the peripapillary RNFL thickness. 18 This observation suggests that under the conditions of their experiment, the reproducibility of the GDx peripapillary RNFL measurements may be insufficient to identify the effect of pupil size on the retardation measurement. Others indicate that nerve fibre layer measurements with the GDx (without corneal compensation) are influenced by drugs affecting pupillary diameter.…”
Section: Eyementioning
confidence: 98%